PENGARUH MOTIVASI, KEDISIPLINAN, KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA, KOMITMEN ORGANISASI SERTA KINERJA PEGAWAI (STUDI DI DINAS PERDAGANGAN TENAGA KERJA KOPERASI USAHA KECIL DAN MENENGAH KABUPATEN KARANGANYAR) - Widyastuti, Eny (STIE AUB Surakarta)
The purpose of this study was to find out empirically influences of motivation, discipline, leadership, organizational culture to job satisfaction and organizational commitment, and influences of motivation, discipline, leadership, organizational culture, job satisfaction and organizational commitment to employee performance in the Dinas Perdagangan Tenaga Kerja Koperasi Usaha Kecil dan Menengah of Karanganyar Regency. The technique of sampling that used in this study was sampling method.The sample that used in this research was 51 respondents. The data collecting technique used observation and questionnaire. The data analytical technique used instrument research test such as validity and reliability tests; linearity test; hypothesis test such as path analysis, t test, F test, coefficient determination and coefficient correlation tests. The instrument test result showed that all of instruments were valid and reliable. The hypothesis result of this study showed that: Motivation had positive and significant influence on job satisfaction, while discipline, leadership and organizational culture had positive but insignificant influence on job satisfaction. Motivation and organizational culture had positive and significant influence on organizational commitment, while leadership had positive but insignificant influence on organizational commitment, and discipline had negative but insignificant influence on organizational commitment. Motivation, leadership, organizational culture and job satisfaction had positive and significant influence on performance, while discipline and organizational commitment had positive but insignificant influence on performance. Motivation, discipline, leadership, organizational culture, job satisfaction and organizational commitment simultaneously are significant influence to employee performance in the Dinas Perdagangan Tenaga Kerja Koperasi Usaha Kecil dan Menengah of Karanganyar Regency. The result of path analysis showed that the direct influence of motivation to performance was more effective rather than the indirect effect both through job satisfaction and organizational commitment. The direct influence of discipline to performance was more effective rather than the indirect effect both through job satisfaction and organizational commitment. The direct influence of leadership to performance was more effective rather than the indirect effect both through job satisfaction and organizational commitment. The direct influence of organizational culture to performance was more effective rather than the indirect effect both through job satisfaction and organizational commitment. Job satisfaction as the variable of intervening in this study was unable to mediate influence of motivation, discipline, leadership and organizational culture variables to performance. Organizational commitment as the variable of intervening in this study was unable to mediate influence of motivation, discipline, leadership and organizational culture variables to performance. The direct influence of leadership to performance was the most dominant path which affected performance. The total effect of leadership to performance through job satisfaction was the most dominant total influence that affected performance.Keywords: Motivation, discipline, leadership, organizational culture, job satisfaction, organizational commitment and performance.